Pesantren Medical: Health Education Management for Santri Towards an Islamic and Healthy Lifestyle - Jasuli Jasuli (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic boarding schools (pesantren) often emphasize religious purity but lack integrated systems to promote hygienic practices. This study addresses the gap by exploring how health education can be managed effectively within a pesantren context to foster a healthy and Islamic lifestyle among santri (students). Using a qualitative case study approach, this research was conducted at Pesantren Nurul Qarnain in Jember, Indonesia. Data were collected through in-depth interviews, participatory observations, and document analysis. Thematic analysis was carried out using Miles and Huberman’s interactive model, with triangulation ensuring credibility. The study identified three key components of successful health education management: (1) participative kyai leadership that models hygiene and spiritual discipline, (2) structured institutional systems including SOPs, hygiene evaluations, and collective routines, and (3) the role of santri husada as internal health cadres who provide peer-based education and monitoring. These elements facilitated the transformation of hygiene behaviors from externally enforced routines into internalized, community-driven habits grounded in Islamic values. The integration of leadership, institutional systems, and peer empowerment created a sustainable health culture. The "Pesantren Medical" model developed through this study offers a culturally embedded, replicable framework for other faith-based residential schools. It demonstrates how religious values, when operationalized through leadership and structure, can drive behavioral change and promote holistic well-being.